ATMPH 2020
DOI: 10.36295/asro.2020.232109
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidative Statues in Sera and Saliva of Iraqi Psoriasis Patients: A Correlation Study

Abstract: Psoriasis is an autoimmune and inflammatory skin disease with reactive abnormal epidermal differentiation, in which genetic and environmental factors have a significant role. The aim of this study to look for the correlation between total oxidant status [TOS], total antioxidant status [TAS] andoxidative stress index [OSI] in serum of psoriatic with that of saliva. A Case study was carried on one hundred psoriatic patients and ninety three healthy individuals. The results showed a highly significantincrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…The results of the present study indicated that the thiol-disulfide status play an important role in the oxidative stress measured previously in the patients included in the study (14) and using the biological drug ETN seems to improve the in-balance observed in this status. Moreover the current data provide evidence of the possibility of using saliva, as an alternative fluid instead of blood serum, to detect changes in the level of some thiol homeostasis related parameters, as well as to follow the impact of ETN treatment on these parameters.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…The results of the present study indicated that the thiol-disulfide status play an important role in the oxidative stress measured previously in the patients included in the study (14) and using the biological drug ETN seems to improve the in-balance observed in this status. Moreover the current data provide evidence of the possibility of using saliva, as an alternative fluid instead of blood serum, to detect changes in the level of some thiol homeostasis related parameters, as well as to follow the impact of ETN treatment on these parameters.…”
Section: Discussionsupporting
confidence: 64%
“…Dynamic/Native ratio, Dynamic/Total ratio and Native/Total ratio parameters in saliva andserum. It has been reported that oxidative stress (OS) play an important role in the pathogenesis of many diseases including inflammatory diseases and some new studies have reported the role of oxidative stress in the pathogenesis of psoriasis [14,18]. The chemotactic effect of ROS on neutrophils contributes to the accumulation of the various inflammatory cells in psoriasis lesions [34], and the ROS generated by TNF-alpha in keratinocytes are responsible for initiating and maintaining chronic inflammation by regulation of certain pathways that are involved in the inflammatory process [15,34].…”
Section: Table 3: Pearson Correlation Between [T-thiol] [N-thiol] [D-...mentioning
confidence: 99%
See 2 more Smart Citations